Sometimes a great notion : a novel - Kesey, Ken (Viking Press, 1964)
The Stampers, a logging family pitted by circumstance against big business, are rough, hard men and women who live by the motto "never give an inch." Added to the turmoil is the return of Leland, a dope-smoking, college educated half brother whose arrival triggers a tidal wave of events that spiral gradually out of control.